Introduction to the study of the Quran: issues, principles and method - Ushama, Thameem (s.n, 2012)
Commencing with Muslim legacy in Ulum al-Quran the research studies names of the Quran and its vocabulary and language, and the relationship between the Quran and Hadith. The Phenomenon of Wahy, whether it is myth or reality is another vital theme.